Sexually transmitted infections and the HPV-related burden: evolution of Italian epidemiology and policy - Gazzetta, Silvia; Valent, Francesca; Sala, Alessia; Driul, Lorenza; Brunelli, Laura (Frontiers in Public Health, 2024)
Sexually transmitted infections (STIs) are a major public health problem worldwide, with a high prevalence between the ages of 15 and 25 in most Western countries. High notification rates of chlamydia, gonorrhea, and syphilis are reported in the WHO European Region, with differences between countries. In Italy, the total number of STIs alerts increased by 18% from 2020 to 2021. HPV is the most common sexually transmitted infection; globally one in seven women is infected by this virus, and certain sexual behaviors are important risk factors for HPV-related cancers, particularly cervical cancer (CC), anogenital cancers and cancers of the head and neck. The burden of CC is relevant worldwide, in particular in Europe CC is the third leading cause of cancer-related deaths in women aged 15–44. This HPV-related tumor is preventable through a combined strategy of vaccination and screening for precursor lesions. In Italy, the coverage of organized screening varies from region to region and the average HPV vaccination rate is still far from the expected optimal threshold of 95% at the age of 12. To address the challenges of health promotion and HPV prevention, priority actions are needed such as: promoting education and information at every level, from schools to healthcare professionals. In Italy, education of adolescents on sexual and reproductive health, still remains critical, regionally inhomogeneous and much lower than in other European countries. Equitable measures need to be taken, and schools are an important place for health promotion activities.